CAN THE TALK TEST BE USED TO PREDICT TRAINING INDUCED CHANGES IN VENTILATORY THRESHOLD? (Kinesiology, 2020)
This study was designed to assess the ability of the Talk Test (TT) to track training-related changes in ventilatory threshold (VT). Thirteen recreational athletes (mean±SD; age, 20.5±1.91 years, (Males=7, Females=6) completed two incremental exercise tests (one with respiratory gas exchange and one with the TT) before and after 6-weeks of self-directed increases in training load. The TT was used to predict VT by assessing the ability to speak comfortably after 3-minute exercise stages based on speech comfort during a 100-word passage. Training load was documented using exercise logs based on sRPE and training duration. Repeated measures ANOVA, with Tukey’s post-hoc analysis, was used to detect differences between the changes in power output at the equivocal stage of the Talk Test and VT measured by gas exchange (p.05). However, the increase in power output at VT (+15.5%) was significantly underestimated by the change in power output at equivocal stage of the TT (+8.0%).  The correlation between changes in power output at VT and PO at the equivocal stage of the TT was r=0.66. However, about 50% of subjects did not change their power output at the equivocal stage of the TT, so the individual correspondence between Talk Test and measured VT was only moderately strong.